Anti-Diabetic Potential of Ocimum gratissimum Leaf Fractions in Fortified Diet-Fed Streptozotocin Treated Rat Model of Type-2 Diabetes - Stanley I. R. Okoduwa; Isamila A. Umar; Dorcas B. James; Hajiya M. Inuwa (Medicines, 2017)
Background: Ocimum gratissimum (OG) is used in the traditional management of diabetes in Nigeria. This study investigated the anti-diabetic potential of OG leaf fractions (OGLF) in a rat model of Type-2 diabetes (T2D). Method: Methanol crude extract of OG leaf was fractionated with solvents of increasing order of polarity (n-hexane, chloroform, ethyl-acetate, n-butanol and water). The anti-diabetic potential of the fractions was evaluated in vivo. T2D was induced in Albino Wistar rats and treated with OGLF. Result: The T2D rats showed significant elevation in serum levels of fasting blood glucose (FBG), liver and kidney function biomarkers. At 4-weeks of intervention with OGLF, the untreated diabetic control group maintained severe hyperglycaemia in the presence of 61.7% serum insulin, 17.3% pancreatic β-cell function (HOMA-β) and 51.5% Insulin sensitivity. The glucose tolerance ability was enhanced in the n-butanol-fraction (OGb) treated group. With 74.8% available serum insulin and 38.6% improvement in insulin sensitivity, the OGb treated group had a 63.5% reduction in FBG and it was found to be most effective as it ameliorates a majority of the changes caused in the studied parameters in diabetic rats. Conclusions: The data from this study suggest that OGb fraction is a potential candidate for the development of an effective drug for the management of T2D.